An alternate level of care plan: Co‐designing components of an intervention with patients, caregivers and providers to address delayed hospital discharge challenges. (30th June 2020) - Kuluski, Kerry; Ho, Julia W; Cadel, Lauren; Shearkhani, Sara; Levy, Charissa; Marcinow, Michelle; Peckham, Allie; Sandercock, Jane; Willison, Donald J; Guilcher, Sara JT
Abstract: Objective: To engage with patients, caregivers and care providers to co‐design components of an intervention that aims to improve delayed hospital discharge experiences. Design: This is a qualitative study, which entailed working groups and co‐design sessions utilizing World Café and deliberative dialogue techniques to continually refine the intervention. Setting and Participants: Our team engaged with 61 participants (patients, caregivers and care providers) in urban and rural communities across Ontario, Canada. A 7‐member Patient and Caregiver Advisory Council participated in all stages of the research. Results: Key challenges experienced during a delayed discharge by patients, caregivers and care providers were poor communication and a lack of care services. Participants recommended a communication guide to support on‐going conversation between care providers, patients and caregivers. The guide included key topics to cover and questions to ask during initial and on‐going conversations to manage expectations and better understand the priorities and goals of patients and caregivers. Service recommendations included getting out of bed and dressed each day, addressing the psycho‐social needs of patients through tailored activities and having a storyboard at the bedside to facilitate on‐going engagement. Discussion and Conclusions: Our findings outline ways to meaningfully engage patients and caregivers during a delayed hospital discharge. Combining this with a minimal basket of services can potentially facilitate a better care experience and outcomes for patients, their care providers and families.